2008
DOI: 10.1007/s10641-008-9395-x
|View full text |Cite
|
Sign up to set email alerts
|

Pectoral fin beat frequency predicts oxygen consumption during spontaneous activity in a labriform swimming fish (Embiotoca lateralis)

Abstract: The objective of this study was to identify kinematic variables correlated with oxygen consumption during spontaneous labriform swimming. Kinematic variables (swimming speed, change of speed, turning angle, turning rate, turning radius and pectoral fin beat frequency) and oxygen consumption (MO 2 ) of spontaneous swimming in Embiotoca lateralis were measured in a circular arena using video tracking and respirometry, respectively. The main variable influencing MO 2 was pectoral fin beat frequency (r 2 =0.71). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The M O 2 value of 100 mg h À1 kg À1 is similar to the SMR estimated from the spontaneous swimming seabream in this study and validates this method for obtaining reliable estimates of SMR. This is in accordance with the study by Tudorache et al (2009). They found that estimating SMR from spontaneous swimming surf perches (Embiotoca lateralis) also resulted in a reliable estimate of SMR.…”
Section: Swimming Costs At U Optsupporting
confidence: 92%
See 1 more Smart Citation
“…The M O 2 value of 100 mg h À1 kg À1 is similar to the SMR estimated from the spontaneous swimming seabream in this study and validates this method for obtaining reliable estimates of SMR. This is in accordance with the study by Tudorache et al (2009). They found that estimating SMR from spontaneous swimming surf perches (Embiotoca lateralis) also resulted in a reliable estimate of SMR.…”
Section: Swimming Costs At U Optsupporting
confidence: 92%
“…Krohn and Boisclair (1994) demonstrated with spontaneously swimming brook trout (Salvelinus fontinalis) that M O 2 correlated equally well with mean speed, acceleration and turning rate. Only few studies aimed to quantify the influence of the different swimming characteristics on M O 2 of spontaneously active fish (Tang and Boisclair 1995;Tang et al 2000;Tudorache et al 2009). Tang and Boisclair (1995) found that the average turning rate and the variance of speed both contributed significantly to the explanation of M O 2 of brook trout.…”
Section: Introductionmentioning
confidence: 99%
“…Mussi et al, 2002;Kendall et al, 2007;Tudorache et al, 2009;Johansen et al, 2010). Some authors have suggested that the relationships between fin-beat frequency, oxygen consumption rate and swimming speed in a given fish species may provide useful indicators of swimming energetics in the wild, which are extremely difficult to estimate in aquatic species (Steinhausen et al, 2005;Ohlberger et al, 2007;Tudorache et al, 2009;Layton, 2011). However, our results suggest that the use of time-averaged fin kinematics to predict oxygen consumption rates depends on the hydrodynamic context in which these estimates are made.…”
Section: Research Articlementioning
confidence: 99%
“…During sound production, the pectoral fins complete a cycle between 15 and 40 ms, corresponding to about 25-60 beats s −1 . This is higher than typical rates observed for locomotion because pectoral fin beat frequencies can be from 20 to 30 Hz in larval and juvenile fishes (Green et al, 2011;Hale et al, 2006) but are generally below 10 Hz in most adult species during swimming (Gibb et al, 1994;Mussi et al, 2002;Tudorache et al, 2008). Alternating pectoral fin motions have also been shown to function during station holding, maneuvering, turning and deceleration in many species (Drucker and Lauder, 2003;Hove et al, 2001).…”
Section: Discussionmentioning
confidence: 95%